Altering bacterial community: A possible way of lactic acid bacteria inoculants reducing CO2 production and nutrient loss during fermentation. (June 2021) - Chen, Dekui; Zheng, Mingyang; Guo, Xiang; Chen, Xiaoyang; Zhang, Qing
Highlights: CO2 production during ensiling with or without additives were investigated. CO2 production was closely correlated with the bacterial communities. L. plantarum could reduce CO2 production by altering bacterial communities. Abstract: CO2 production during ensiling is a source of greenhouse gases emissions and a cause of nutrient loss of silage. To investigate the influence of additives on CO2 production and relevant bacterial communities, stylo and rice straw were ensiled with sucrose and Lactobacillus plantarum (LP). After 30 days fermentation, LP reduced CO2 production (from 66.2 to 0 mL/100 g fresh matter in stylo, from 83.7 to 16.6 mL/100 g fresh matter in rice straw) and weight loss (from 2.71 to 1.72% in stylo, from 2.75 to 2.40% in rice straw). CO2 production was positively correlated ( P < 0.05) with Lactococcus (0.99), Leuconostoc (0.55), Lachnoclostridium (0.45), Prevotella (0.23) and was negatively correlated ( P < 0.05) with Serratia (-0.66), Sphingobacterium (-0.58), Pediococcus (-0.36). LP decreased the relative abundance of genera positively correlated with CO2 production and increased that of genera negatively correlated. In conclusion, LP could reduce CO2 production by altering bacterial community during ensiling.